Restrictive clonal allocation in the chimeric mouse brain - Kuan, Chia-Yi (The National Academy of Sciences of the USA, 1997)
Whether, and to what extent, lineage restriction contributes to the organization of the mammalian brain remains unclear. Here we address this issue by examining the distribution of clonally related cells in chimeric mice generated by injecting genetically tagged embryonic stem (ES) cells into blastocyst embryos. Our examination of postnatal chimeric brains revealed that the vast majority of labeled ES cell descendents were confined within a different subset of brain regions in each animal. Moreover, the deployment of labeled cells in different brain regions was distinctive. The pattern of ordered and binomial colonization suggested that early diversified founder cells may constrain the fates of their descendants through a restriction of dispersion. In addition, the symmetrical distribution of ES cell descendants suggests that bilaterally corresponding structures may arise from a common set of progenitor cells. Finally, clones of cells formed a continuous band within the deep strata of the neocortex. This later finding in conjunction with the radial distribution of clones in remaining layers observed in previous studies indicates that the cerebral neocortex may derive from two groups of founder cells, which is consistent with the hypothesis of dual phylogenetic origins of the mammalian cerebral cortex.